2013
DOI: 10.1089/vbz.2012.1234
|View full text |Cite
|
Sign up to set email alerts
|

Environmental, Climatic, and Residential Neighborhood Determinants of Feline Tularemia

Abstract: Background: Tularemia, caused by a Gram-negative bacterium Francisella tularensis, is an occasional disease of cats in the midwestern United States and a public health concern due to its zoonotic potential. Different environmental, climatic, and pet-owner's housing and socioeconomic conditions were evaluated as potential risk factors for feline tularemia using Geographic Information Systems (GIS) in a retrospective case-control study. Methods: The study included 46 cases identified as positive for tularemia ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 26 publications
(25 reference statements)
2
12
0
Order By: Relevance
“…The medical significance of this tick species has been discussed amply [1, 32]: lone star ticks are the most frequently encountered ticks by humans in some parts of the US, particularly in the southern and central Midwest [33, 34]. This species is a growing public health concern since spatiotemporal dimensions of several lone star tick-transmitted diseases appear to be worsening [3537]. Lone star ticks are well-known as a vector of human ehrlichiosis [38] and Southern Tick Associated Rash Illness [39], but recent laboratory and field investigations have confirmed that the recently discovered human pathogens Heartland Virus (HRTV) and Bourbon Virus (BRBV) are also transmitted by nymphs of this species [4042].…”
Section: Discussionmentioning
confidence: 99%
“…The medical significance of this tick species has been discussed amply [1, 32]: lone star ticks are the most frequently encountered ticks by humans in some parts of the US, particularly in the southern and central Midwest [33, 34]. This species is a growing public health concern since spatiotemporal dimensions of several lone star tick-transmitted diseases appear to be worsening [3537]. Lone star ticks are well-known as a vector of human ehrlichiosis [38] and Southern Tick Associated Rash Illness [39], but recent laboratory and field investigations have confirmed that the recently discovered human pathogens Heartland Virus (HRTV) and Bourbon Virus (BRBV) are also transmitted by nymphs of this species [4042].…”
Section: Discussionmentioning
confidence: 99%
“…variabilis is one of the most medically significant tick species that transmit disease-causing pathogens to humans and animals in North America [e.g., 47 , 48 ]. Spatiotemporal patterns of county-level incidences for some of the diseases transmitted by this tick species, tularemia [ 49 ], bovine anaplasmosis [ 10 ], and Rocky Mountain spotted fever (RMSF) [ 9 ] have worsened steadily over the past decade, indicating a steady increase in disease burden likely related to this tick species. Such increases in incidences could be related to several factors: better disease surveillance programs at state and local levels, expansion of non-Lyme tick-borne diseases on the Centers for Disease Control and Prevention (CDC)’s reportable diseases list, improved diagnostic methods, and increased awareness of, and interest in tick-borne diseases among physicians and patients, to name a few.…”
Section: Discussionmentioning
confidence: 99%
“…Other diseases vectored by these ticks could also be increasing in the region. The number of cases of feline tularemia (Raghavan et al 2013) and cytauxzoonosis (Raghavan et al 2014b) in the region diagnosed at the Kansas State Veterinary Diagnostic Laboratory (KSVDL) have increased steadily over the years, at least partly owing to the wider geographic distribution of A. americanum. An important contributing factor for the current distribution of this species in the state and increases in A. americanum-vectored diseases could be the almost exponential population increase of their primary host, the whitetailed deer, in Kansas in the past two decades (Paddock andYabsley 2007, Kansas Department of Wildlife, Parks andTourism [KDWP] 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence suggests that the disease agents transmitted by A. americanum ticks in Kansas may be increasing (Raghavan et al 2013(Raghavan et al , 2014. The spatio-temporal pattern of human monocytic ehrlichiosis, vectored by A. americanum, used to be concentrated in the southeastern counties in the state but is now reported commonly from most eastern and many central Kansas counties (Raghavan et al 2014).…”
Section: Introductionmentioning
confidence: 99%